2020
DOI: 10.1186/s12935-020-01596-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets of Yangyin Fuzheng Jiedu Prescription in the treatment of hepatocellular carcinoma based on network pharmacology analysis

Abstract: Background Yangyin Fuzheng Jiedu Prescription (YFJP) is a traditional Chinese medicine (TCM) indicated for the treatment of hepatocellular carcinoma (HCC). Its potential targets and molecular mechanisms are not clear. Therefore, this study intends to explore the molecular mechanism of YFJP based on network pharmacology analysis and in vitro validation. Methods and results Through univariate and multivariate analyses and survival anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…It is well known that flavonoids have a protective effect on HCC, and different flavonoids can play a role in the treatment of HCC by inhibiting tumor growth and exerting anti‐metastasis, anti‐angiogenesis, and anti‐inflammatory effects 41 . This result is consistent with our previous studies, in which HMM and RB in YFJP were found to improve the suppression of the TME 42 . To obtain HCC‐related targets, five databases were used.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…It is well known that flavonoids have a protective effect on HCC, and different flavonoids can play a role in the treatment of HCC by inhibiting tumor growth and exerting anti‐metastasis, anti‐angiogenesis, and anti‐inflammatory effects 41 . This result is consistent with our previous studies, in which HMM and RB in YFJP were found to improve the suppression of the TME 42 . To obtain HCC‐related targets, five databases were used.…”
Section: Resultssupporting
confidence: 88%
“…With the recognition of the importance of remodeling the immune microenvironment for the treatment of HCC, the immunomodulatory effects of TCM have increasingly received attention in recent years. Previous studies by our team have shown that YFJP acts on multiple HCC‐related genes to inhibit tumor progression 42 . In vivo experiments have also confirmed that the mechanism of the antitumor effect of YFJP involves alleviating CD8 + T cell exhaustion and improving the immunosuppressive HCC microenvironment 14 .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, suppression of VEGFA activation may enhance the therapeutic effectiveness of ovarian tumour chemotherapy through inhibition of autophagy related to VEGFA ( 38 ). It has been shown preclinically that targeting VEGFA activity or its signalling pathway is one of the pharmacological mechanisms of action of traditional Chinese medicines in cancers ( 39 , 40 ). However, the biological mechanisms of anti-ovarian cancer effects of mogroside V associated with VEGFA remain unreported.…”
Section: Discussionmentioning
confidence: 99%